Avaliação comparativa do uso crônico do alendronato de sódio e do ácido zoledrônico em sítios pós-exodontia na mandíbula de ratos - Isaias, Pedro Henrique Chaves (2020)
Alendronate sodium (ALN) and zoledronic acid (ZA) are bisphosphonates (BP) with wide clinical use, but are associated with bisphosphonate-induced jaw osteonecrosis (BRONJ). To avoid BRONJ, the suspension of BP prior to extraction is still an uncertain method, controversial and without well-defined clinical protocols. Animal models of chronic BP treatment involving ALN and associated with extraction are not standardized, do not use human-compatible doses and often do not use the same route of administration, as has been done in some animal models administered with ZA. Thus, a comparative study with models using both BP is important to analyze similarities and differences in post-extraction alveolar healing situations. The aim of this study is to compare clinical, radiographic, histopathological and immunohistochemical aspects of experimental models with chronic BP treatment in rats using ALN and ZA. For this, 48 male Wistar rats (180–200 g) were divided into different experimental groups (n=6). All animals administered ZA were submitted to the same experimental protocol with three weekly intravenous infusions of 0.2 mg/kg, followed by extraction and one additional post-extraction infusion. The animals treated with ALN received different weekly oral doses of the drug (2.5 mg/kg, 5.0 mg/kg or 7.5 mg/kg) and were subdivided into groups with continuous and discontinuous administration before the surgical procedure of dental extraction. The negative control group consisted of animals treated with saline (0.1 m /kg) weekly by gavage. After 70 days of protocol, the animals were euthanized, being performed leukocyte analysis, radiographic, histopathological, histomorphometric and immunohistochemical exams (TNF-α and TRAP) of the extraction sites. As a result, we found that the radiolucent appearance of the alveoli in the continuous ALN groups was more evident than in the saline group; however, a larger significant radiolucent area at the extraction site was observed only in the ZA group compared to all other groups (p=0.007). Smaller area of bone tissue filling the socket cavity after extraction was observed in the continuous ALN (7.5 mg/kg) and ZA groups compared to the other groups (p<0.001). Number of empty osteocyte lacunae was more significant in ZA group compared to all other groups, however, continuous ALN groups showed higher number of empty osteocyte lacunae in relation to saline control (p<0.001). Vacuolated osteoclasts were seen in greater numbers in continuous ALN groups (5.0 mg/kg and 7.5 mg/kg) compared to other ALN-treated and saline groups, however, the ZA group had a higher number of vacuolated osteoclasts among all other groups (p=0.004). All ALN groups exhibited a higher presence of mononuclear inflammatory cells than the saline group, however, the ZA group showed even larger and statistically different numbers than all other groups (p=0.018), especially in relation to polymorphonuclear inflammatory cells (p<0.001). Immunohistochemical analysis for TNF-α was significant in the groups treated with discontinuous ALN 7.5 mg/kg, continuous ALN at 2.5 mg/kg, 5.0 mg/kg, 7.5 mg/kg and in ZA than the control group. TRAP positive osteoclasts were significantly higher in the continuous ALN 5.0 mg/kg, 7.5 mg/kg and ZA groups (p<0.001) than the control group. In short, continuously administered ALN decreases post-extraction alveolar bone healing in rats, especially at high doses. Such effects also occurred when ZA was used, however to a greater degree and with associated necrosis. Discontinuation of ALN does not imply significant changes in alveolar healing.